-7x+6-9x=6

Simple and best practice solution for -7x+6-9x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+6-9x=6 equation:


Simplifying
-7x + 6 + -9x = 6

Reorder the terms:
6 + -7x + -9x = 6

Combine like terms: -7x + -9x = -16x
6 + -16x = 6

Add '-6' to each side of the equation.
6 + -6 + -16x = 6 + -6

Combine like terms: 6 + -6 = 0
0 + -16x = 6 + -6
-16x = 6 + -6

Combine like terms: 6 + -6 = 0
-16x = 0

Solving
-16x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-16'.
x = 0

Simplifying
x = 0

See similar equations:

| 3(5.45)-7y=3 | | 10c-14=86 | | 14y=-14x-56 | | 49+x=x^2+2x+1 | | 6p+8=62 | | -2c+1=0 | | 7x+8x=-10+5x | | 14=49y | | x+(x+1)+(x+2)=128 | | 2x+-4=10 | | p/2=p-6 | | h(t)=20t-5t^2 | | 27=6b | | -5.5x-20=5.5x+24 | | ^3-2x/^4x=2 | | 3860+x=4135 | | 2(2x-6)=14 | | 5+(8)n=29 | | 9c+5=18-4c | | x^2+15x=8x+60 | | 6(r+8)=18 | | 14-y= | | 2y+24=3x | | 6p+8= | | 5+(-4)n=25 | | p/2−2=p-8 | | 13u=63+4u | | 20g+24h= | | -10+7y=x | | 4x+2f(x)=9 | | 18-y=5y | | 3g+1=7g-19 |

Equations solver categories